Exchange rates and global imbalances: the importance of asset valuation effects and interest rate changes - Christian M. Oberpriller (Kiel Institute for the World Economy (IfW), 2007)
this paper analyzes two effects which might have an important impact on a reduction of global external imbalances. These are valuation effects on the one hand and interest rate effects on the other hand. We use a four-region model that is based on the models by Obstfeld and Rogoff (2005) and Oberpriller (2007) to analyze the difference in the occurring exchange rate changes with and without valuation and interest rate effects under two different scenarios of narrowing global imbalances. The outcome is a reduced need for real dollar depreciation because the United States will largely benefit from valuation gains on their foreign assets while the effect that stems from interest rate changes works in the opposite direction but is not as strong as the valuation effect. The magnitude of valuation and interest rate effects reduce the need for real exchange rate depreciation by two to four percentage points.
Keywords: F31; F32; F41; 330; current account; exchange rates; valuation effects; global imbalances; Kaufkraftparität; US-Dollar; Zahlungsbilanzungleichgewicht; Vermögen; Bewertung; Zinsparität; Welt